"To have" and "To be" attitudes in secondary school students - Ilona Szostak-Jośko (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
In the world of continual social and economic changes, morality crisis, consumptionism, the contrast between "to be" and "to have" attitudes is manifesting itself. The aim of this study was to reveal what values are preferred by secondary school students. Results of the research, obtained with the Scale of "to be" and "to have" Attitudes by Bronisław Grulkowski, show that ¾ of students participating in this study identifies with the attitude on a border of those groups. It means that gaining pleasure, collecting material goods, life and financial stabilisation, conformity are as important for the respondents as friendship, solidarity with others, giving help to people in need, self-improvement, developing one's interests or broadening one's knowledge. Received results provided a foundation for indications for the educational practice in the realm of enrichment and development of attitudes recognising the primacy of human spiritual values.